Creating a Lifestyle Medicine Specialist Fellowship: A Replicable and Sustainable Model. Issue 3 (May 2020) - Rea, Brenda; Wilson, April
As new specialties emerge in medicine, certification pathways must be defined and formalized. The Lifestyle Medicine Physician certification, including both experiential and educational pathways, have been in place for several years. Although raising competence across all specialties through the Lifestyle Medicine Physician Diplomates to a foundational level is essential, additional expertise must be attained to be a true Lifestyle Medicine Specialist as outlined by the American Board of Lifestyle Medicine. This column will describe how Loma Linda University Health (LLUH) created a Lifestyle Medicine Specialist Fellowship that meets the educational pathway requirements for the Lifestyle Medicine Specialist certification and how it can be replicated and sustained at other training sites across the nation.